Shabana and the Baby Goat - Samina Mishra (Bharat Tulika Publishers, 2024)
* A lovable look at pets and their little quirks that make them ours * The simple storyline about friendship and playful, repetitive text makes it ideal for the age group * Sprightly, happy pictures match the spring in Shabana and Kajri$1 (Bs steps! * Told with a filmmaker$1 (Bs flair for visual detail * Bright ideas and best friends -- a story that all children will love!s
Keywords: EY - RM -- EY - RM